The Effect Of Centrifugation Speed On The Results Of Urine Sediment Examination: Hubungan Pengaruh Kecepatan Sentrifugasi Terhadap Hasil Pemeriksaan Sedimen Urine - Hasanah, Muslimah Uswatun; Puspitasari, Puspitasari (Universitas Muhammadiyah Sidoarjo, 2022)
The process of centrifugation in urine examination is very important because it can be used in the manufacture of urine sediment. The purpose of this study was to determine the effect of centrifugation speed on the results of urine sediment examination. Centrifugation speeds used were 3000 rpm, 3500 rpm, 4000 rpm, and 4500 rpm using pathological urine samples. The samples used were 32. The research method used was an experimental laboratory at the Pusura Yos Sudarso clinical laboratory in Surabaya. The results of the study with a speed of 3000 rpm obtained an average of erythrocytes = 6.63/LPB, leukocytes = 13.63/LPB, and epithelial = 10.50/LPB. At a speed of 3500 rpm the average value of erythrocytes = 7.63/LPB, leukocytes = 15.13/LPB, and epithelium 11.63/PLB. At a speed of 4000 rpm the average value of erythrocytes = 8.63/LPB, leukocytes = 17.75/LPB and epithelial = 13.50/LPB. At a speed of 4500 rpm the average value of erythrocytes = 9.63/LPB, leukocytes = 20.50/LPB, and epithelial = 15.38/LPB. The results of the statistical test One Way Anova obtained p-value results of 0.001 < (0.05) in erythrocyte cells, p-value results for leukocytes 0.025 < (0.05), and p-value results for epithelial cells 0.002 < (0.05) means that there is an effect on the centrifugation speed on the results of urine sediment examination.